Investigating English Teachers’ Understanding of English Language Assessment at UPT SMA Negeri 1 Parepare - Usman, Muhammad Syahid; Magdahalena Tjalla; Abdul Haris Sunubi; Ambo Dalle; Zulfah (Universitas Muhammadiyah Palu, 2024)
There are instances where teachers encounter confusion when distinguishing between the terms of assessment, test, evaluation and examination. Moreover, the teachers' understanding of these terms also plays a critical role for students. Based on the reasons above, this research aimed to describe the English teachers’ understanding of English language assessment and how the teachers assess the students’ work. The research was conducted at UPT SMA Negeri 1 Parepare. There were five English teachers as research subjects. The research method used qualitative design. The data collected through interview. The interview results were transcribed, then analyzed qualitatively by reducing data based on the research questions. The data that has been reduced is then converted into narrative text, making it easy to understand. The last was making conclusion and suggestion based on the data obtained. The research findings revealed that, there were differences and similarities in the understanding. Four teachers showed differences, with only one teacher had relevant understanding toward the assessment understanding. The other four teachers, in addition to assessment understanding, also had understanding relevant to instructional, subject matter, and pedagogical. The data indicated that Assessment understanding was the most dominant among the five teachers, suggesting that all the teachers were able to differentiate testing, examination, and evaluation. Furthermore, the teachers prioritized their assessment in learning to students by using a variety of assessment methods such as daily tests, semester exams, attitude assessments, as well as group activities and projects to enhance students confidence and encourage active learning in the classroom.